Analisis Kesenjangan Kompetensi Dan Harapan Pengguna Lulusan Perbankan - Nani Cahyani; Budi Harni; Suparman Suparman (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2017)
This study aims to determine the level of competence of STIE Kesatuan’s graduates in the corporate perspective. This study used survey method. Measurement gap analyzed by comparing the facts to standards. The Respondents of this research are 30 head of banks in Bogor. The results showed that the quality of the graduates as a whole has been good. Based on the average value (3.8000), the GAP between the expectations and the reality is low.